Rise of teledermatology in the COVID-19 era: A pan-world perspective. (February 2022) - Naik, Piyu Parth
Objective: During the coronavirus disease pandemic, enforced restrictions prevented face-to-face consultations for patients requiring non-emergency medical treatment. In response, there was a rise in telemedical practices, such as teledermatology. This study aimed at understanding the pan-world experiences of patients and healthcare staff who adapted to teledermatology in the coronavirus disease era. Methods: This study made use of an online survey presented to dermatology professionals using social media and WhatsApp groups. Professionals who applied teledermatology between March and June 2020 were targeted. The survey was designed to identify respondent demographics and the preferred platforms for digital consultations. The most common diagnoses and rates of referral for further evaluation were recorded. Lastly, a platform was provided for practitioners to report their own and their patient's perspectives on the advantages and operational challenges of teledermatology. Data were collated and analyzed in Microsoft Excel. Results: In total, 653 stakeholders participated, representing countries worldwide. Facebook and WhatsApp services were the most popular mediums of digital consultation. Diagnoses of ailments, such as acne and eczema, as well as skin-related infections, were most common. Of the cases referred for biopsy, 10 patients were subsequently diagnosed with cutaneous malignancies. Practitioners and patients not only reported personal benefit from adopting teledermatology, but also reported concerns regarding data privacy and the levels of technological literacy required. Conclusions: Teledermatology proved an innovative clinical response to unprecedented challenges. However, further policy development and technological advancement aimed at increasing the diagnostic power of digital consultations are needed to support the continuation of teledermatology in the post-pandemic world.